The architectural works of beneficence in Mar del Plata (Argentina) as disciplinary devices (1900-1930). Analysis through Foucault's perspective - Fiorentino, Romina (Universidad ORT Uruguay, 2019)
This work is part of the research carried out in the Heritage Group of the FAUD-UNMDP, with respect to the Preservation of the Architectural Heritage of Welfare and the Doctorate of Social Work. Two architectural works constructed by the Society of Charity in Argentina, located in the city of Mar del Plata, such as the “Solarium” (today demolished) and the current “Saturnino Unzué Institute” (formerly the the city, declared a National Monument) that were built at the beginning of the 20th century. These buildings are analyzed from the Foucaultian perspective of power, as “disciplinary devices” implanted within the city, with respect to the historical process of construction of the modern State.On the other hand, it is noteworthy that these works, beyond their architectural values, have a great “testimonial value” as historical documents in themselves, since they are spatial enclaves in which the passage of the different paradigms of assistance converge social throughout its history. For this study different documentary and bibliographical sources were taken, among them albums of the same Society of Beneficence, planimetry and historical photos, that allow to see these problems expressed in the history of its walls, its documents and regulations.